2015
DOI: 10.1155/2015/198657
|View full text |Cite
|
Sign up to set email alerts
|

A Generalization of Electromagnetic Fluctuation-Induced Casimir Energy

Abstract: Intermolecular forces responsible for adhesion and cohesion can be classified according to their origins; interactions between charges, ions, random dipole-random dipole (Keesom), random dipole-induced dipole (Debye) are due to electrostatic effects; covalent bonding, London dispersion forces between fluctuating dipoles, and Lewis acid-base interactions are due to quantum mechanical effects; pressure and osmotic forces are of entropic origin. Of all these interactions, the London dispersion interaction is univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Lifshitz used Rytov's theory of fluctuational electrodynamics to determine the force between two semi‐infinite half‐spaces separated by a vacuum gap (a planar cavity). Recent works have shown that the generalization of Lifshitz theory can be applied not only to the multilayered media , but also to the objects of arbitrary shapes , such as ellipsoids , cylinders and cubes . In this work, we find the van der Waals contribution to pressure within a cavity of vapor, the electromagnetic properties of which is assumed to be identical with that of vacuum, in a homogeneous, isotropic, infinite liquid (see Fig.…”
Section: Introductionmentioning
confidence: 88%
“…Lifshitz used Rytov's theory of fluctuational electrodynamics to determine the force between two semi‐infinite half‐spaces separated by a vacuum gap (a planar cavity). Recent works have shown that the generalization of Lifshitz theory can be applied not only to the multilayered media , but also to the objects of arbitrary shapes , such as ellipsoids , cylinders and cubes . In this work, we find the van der Waals contribution to pressure within a cavity of vapor, the electromagnetic properties of which is assumed to be identical with that of vacuum, in a homogeneous, isotropic, infinite liquid (see Fig.…”
Section: Introductionmentioning
confidence: 88%